Computed tomography findings of arc-welders' pneumoconiosis: Comparison with silicosis. Issue 107 (October 2018) - Takahashi, Masashi; Nitta, Norihisa; Kishimoto, Takumi; Ohtsuka, Yoshinori; Honda, Sumihisa; Ashizawa, Kazuto
Abstract: Objective: Arc-welders' pneumoconiosis (AWP) is a less fibrogenic pneumoconiosis with radiographic shadows that can improve after isolation from dusty environments. Therefore, early diagnosis is important. However, the exact role of chest radiograph and computed tomography (CT) for diagnosing AWP is not fully understood. This study was performed to assess the CT appearance of AWP using semi-quantitative methods and to compare the findings with those of silicosis. The profusion of pulmonary abnormality on chest radiograph were also compared with the semi-quantitative CT score. Materials and methods: Sixty-six patients with clinically diagnosed AWP were included and compared with 33 patients with silicosis. The CT images were interpreted according to the International Classification of HRCT for Occupational and Environmental Respiratory Diseases (ICOERD). Data on the profusion score by chest radiograph were also compared with CT score. Results: Ill-defined centrilobular nodules, ground-glass opacity (GGO) and centrilobular branching opacity were more frequently observed (p = 0.0031) in AWP, whereas well-defined rounded opacity (p < 0.0001), progressive massive fibrosis (p < 0.0001), and mediastinal lymphadenopathy (p < 0.0001) were more frequently observed in silicosis. Regarding lung nodules, there was a high correlation between the ICOERD and CXR profusion scores in silicosis, but CXR underestimated AWP. Conclusion: Ill-defined centrilobular nodules, GGO and centrilobular branching opacity were more frequently observed in AWP than silicosis. Because these findings are difficult to detect by chest radiograph, CT should be considered for the assessment of patients with suspected AWP.